The antenna system for the Multifrequency Scanning MicrowaveRadiometer (MSMR). - Sharma, Shashi Bhushan
This paper presents the design and development of an antenna system for the Multi-frequency Scanning Microwave Radiometer (MSMR) payload, flown on Oceansat-1, in May, 1999. The antenna was designed to meet stringent specifications of a very low cross-polarization level, high beam efficiency, good pattern symmetry, and low VSWR, at four widely separated frequency bands. It used a common aperture-feed system, consisting of a corrugated horn along with an eight-port orthomode transducer. The calculated as well as the measured electrical performance are presented.
Keywords: Microwave radiometry; Multifrequency antennas; Satellite antennas; Corrugated horn antennas; Mode matching methods; Offset reflector antennas; Remote sensing